At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

1(x) = -2x^2-x g(x) = -2x-5 Find (fog)(-6)

Sagot :

Weare given the functions:

f(x) = - 2 x^2 - x

and

g(x) = - 2 x - 5

Find (fog)(-6)

so we recall that the composition fog is the same as finding f (g(x))

so we first find g(-6) = - 2 (-6) - 5 = 12 - 5 = 7

now we apply this to the function f(x)

f (7) = - 2 * 7^2 - 7 = -2 (49) - 7 = -105